Metastatic bone lesion due to methotrexate and etanercept 24 years after breast cancer treatment. (12th April 2014) - Yano, Shuichi
Abstract : A 72-year-old woman with rheumatoid arthritis presented with lumbar vertebral bone metastasis 24 years after mammectomy and radiotherapy for breast cancer. She was treated with prednisolone and methotrexate (MTX) for 11 months to which 10 mg of etanercept twice a week was added for a further 8 months. On the basis of this result, the possibility of a metastatic bone lesion appearing many years after cancer treatment should be considered when planning MTX and etanercept therapy.